Terrestrial mammals of Mozambique : current knowledge and future challenges for conservation - Neves, Isabel Maria Queirós das (2020)
Nations must know on what and where to conserve, as required by Convention on Biological Diversity. Only by knowing where we should trust our knowledge of species occurrence, we will be able to make accurate decisions and efficiently allocate the limited resources for improving quality and coverage of species occurrence and distribution and safeguarding biodiversity. Existing knowledge about the biodiversity of Mozambique is scarce across most taxonomic groups. Long periods of armed conflict seriously affected wildlife and scientific research, contributing to this lack of knowledge. This doctoral thesis aimed to compile and map current knowledge about the occurrence of terrestrial mammal fauna in Mozambique, to discuss the challenges for biodiversity conservation in the country. To meet these objectives, an inventory on terrestrial mammal presence was compiling integrating primary species-occurrence data from 1) the GBIF portal; 2) natural history collections; 3) recent survey reports, and 4) scientific literature. The first part of this thesis focuses on the update of the list of terrestrial mammal species reported for the country. The second part investigates the data bias and gaps in knowledge regarding the distribution of terrestrial mammals in Mozambique, providing priority areas for future surveys. The third part offers a first assessment on the effectiveness of Mozambique’s conservation areas to protect the lesser-known taxa given global change and further suggests priority areas for conservation. As a final contribution of this research, we discuss the contribution of different data sources to the inventory and the importance of digitization and mobilization of biodiversity data in poorly studied countries. Overall, the study developed in this thesis is an important starting point and a valuable resource for understanding the occurrence and distribution of terrestrial mammals in Mozambique, contributing with a dataset now acessible for researchers and decision-makers.